Experimental investigation on gasification characteristics of polycarbonate (PC) microplastics in supercritical water. Issue 2 (April 2020) - Bai, Bin; Liu, Yigang; Meng, Xianghai; Liu, Changlong; Zhang, Hua; Zhang, Wei; Jin, Hui
Abstract: In order to solve the problem of marine microplastics and realize the harmless resource utilization of plastics, the gasification experiments of polycarbonate (PC) microplastics were carried out in supercritical water and a novel seawater gasification of microplastic experiment was investigated. In this paper, the effects of different operating conditions (temperature, time, feedstock concentration, pressure) on gasification performance were discussed. The gasification kinetic of microplastics in supercritical water was calculated. The experimental results showed that the increase in gasification temperature and time enhanced the cracking reaction and free radical reaction of the microplastics to increase the gasification efficiency, while the reduction in feedstock concentration improved the gasification efficiency by increasing the gasification level of unit feedstock. The change in pressure had no significant effect on gasification due to the fact that the properties of the supercritical water were not significantly changed. It was found that the valuable results that all alkali metal salts in seawater promote hydrogen conversion, while in terms of carbon conversion, only KCl, CaCl2, NaHCO3 and seawater had a significant catalytic effect on the gasification. Seawater gasification of microplastics was a potential resource utilization method. Finally, it was considered that the PC plastic gasification conformed to the random nucleation and subsequent growth model (n = 3), and the reaction activation energy was 230.45 kJ/mol, which was smaller than that of traditional pyrolysis. Graphical abstract: Image 1 Highlights: Seawater gasification of microplastics was studied in supercritical water. The effects of different operating conditions on gasification were investigated. A novel result was that seawater promoted the conversion of microplastics. Gasification of PC microplastics conformed to random nucleation model.